2016
DOI: 10.1111/apt.13556
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: faecal occult blood tests show lower colorectal cancer detection rates in the proximal colon in colonoscopy‐verified diagnostic studies

Abstract: Faecal occult blood tests, both guaiac- and immunochemical-based, show better diagnostic performance for the relative detection of colorectal cancer in the distal colon than in the proximal bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 49 publications
(75 reference statements)
2
54
4
Order By: Relevance
“…Therefore, the cancer location (right-sided vs. left-sided) might affect FIT sensitivity. 26,[30][31][32][33] In the present study, the frequency of right-sided location was significantly higher in Negative advanced CRC than in First advanced CRC, indicating that FIT is not accurate enough to detect advanced CRC in the right-sided colon. Overall, these data are in agreement with previous studies that found a lower FIT accuracy for right-sided versus left-side advanced neoplasia.…”
Section: Discussioncontrasting
confidence: 71%
“…Therefore, the cancer location (right-sided vs. left-sided) might affect FIT sensitivity. 26,[30][31][32][33] In the present study, the frequency of right-sided location was significantly higher in Negative advanced CRC than in First advanced CRC, indicating that FIT is not accurate enough to detect advanced CRC in the right-sided colon. Overall, these data are in agreement with previous studies that found a lower FIT accuracy for right-sided versus left-side advanced neoplasia.…”
Section: Discussioncontrasting
confidence: 71%
“…One potential explanation for this may be differences in the size, site and stage of CRCs detected through surveillance relative to screening. A systematic review with meta-analysis by Hirai et al 109 found lower sensitivity of FIT for proximal than distal CRC. Furthermore, faecal haemoglobin levels appear to be higher in patients with larger AAs and in those with a greater number of AAs.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective randomized controlled trials showed that FOBT screening reduced CRC-related mortality [23]. Furthermore, recent fecal immunochemical test (FIT) has shown high CRC detectability [24], while the utility of stool-based DNA assays has been reported as a new application for CRC diagnosis [25]. Nonetheless, FOBT has some limitations, such as its relatively low sensitivity for early-stage or proximal colon cancer [24, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent fecal immunochemical test (FIT) has shown high CRC detectability [24], while the utility of stool-based DNA assays has been reported as a new application for CRC diagnosis [25]. Nonetheless, FOBT has some limitations, such as its relatively low sensitivity for early-stage or proximal colon cancer [24, 26]. Moreover, adherence rate to the CRC screening program based on FOBT and colonoscopy remains low at around 50% [27, 28], and it is reported that many people who avoid current FOBT program prefer a simple blood-based test instead [29].…”
Section: Discussionmentioning
confidence: 99%